Electricity Production From Peat Water Uses Microbial Fuel Cells Technology - Lisa Utami; Lazulva Lazulva; Yuni Fatisa (Universitas Negeri Medan, 2019)
This study aims to study how the potential of peat water as a source of electrical energy using Microbial Fuel Cell (MFC) technology. Observations were made on two chamber vessel reactors (anodes and cathodes) and connected to electrochemical cell circuits (voltaic cells) and voltage values were measured, current, power density generated from the circuit for 9 days.The results of the measurement of the maximum voltage value, the maximum current generated and the maximum power density (8th day) of the reactor are obtained as follows: 50.8 mV, 1 µA and 3.64 x 10-2 mW / m2